Improving maintenance processes with distributed monitoring systems - Fleischmann, Hans; Kohl, Johannes; Franke, Jörg; Reidt, Andreas; Duchon, Markus; Krcmar, Helmut (IEEE International Conference on Industrial Informatics (INDIN), 2016)
Industrial production systems meet strict requirements regarding availability, process control and condition monitoring. As a key enabler of Industry 4.0, cyber-physical systems form the core of a modular, web-based framework, which delivers more efficient condition monitoring mechanisms for maintenance staff in production facilities. The present approach illustrates the potential of a decentralized and centralized, distributed system by using standardized communication protocols and semantic information models. The use of web-based platforms like node.js and protocols such as OPC UA offers the ability to automate transferring information about anomalies, root causes and nominal data directly between cloud-based services and condition monitoring systems on the shop floor. To conclude, a validation is accomplished within a case study on a flexible handling unit.
CRIS-Team Scopus Importer:2023-03-07